Conducting polymer based hybrid nano-composites for enhanced corrosion protective coatings - Patil, R. C.; Radhakrishnan, S. (Progress in Organic Coatings, 2006)
Hybrid composite coatings containing zinc oxide (ZnO) and polyaniline (PANI) as nano-additives dispersions were prepared with poly(vinyl acetate) (PVAc) as the major matrix. The steel plates dip-coated with these formulations were tested for corrosion protection by immersion in saline water over long periods. The Tafel plots for the determination of open circuit potential (OCP) and corrosion current (I-corr) were recorded. The coatings containing both ZnO and PANI showed improved corrosion resistance as compared to the single component coating. The I-corr values of PVAc-ZnO-PANI are found to be two-order magnitude lower than that of PVAc and PVAc-ZnO coatings. The results are explained on the basis of enhancement in barrier properties due to nano-particulate additives in PVAc-ZnO-PANI film together with the redox behaviour of PANI and protective oxide layer formation near the substrate. (C) 2006 Elsevier B.V All rights reserved.
Keywords: Coatings; corrosion; nano-additives; polyaniline; ZnO

CO sensor based on polypyrrole functionalized with iron porphyrin - Paul, Santhosh; Amalraj, Francis; Radhakrishnan, S. (Synthetic Metals, 2009)
Polypyrrole (PPy) was chemically functionalized with 5,10,15,20-tetraphenyl-21H,23H-porphyrin iron(III) chloride (FeTPPCl) with special interest on noxious carbon monoxide (CO) gas in ppm level. Controlled functionalization of PPy was achieved with incorporation of various concentrations of porphyrin. The resulted semiconducting material was well characterized by different techniques such as UV-vis spectroscopy, FTIR, GFAAS, XRD, and EDAX. The functionalized polypyrrole material on interdigitated electrode was experienced an immediate increase in resistance when exposed to carbon monoxide gas at very low concentration. The CO gas interacted very fast with the FeTPPCl functionalized PPy at room temperature (RT) and then slowly saturated. The response of these materials was not unidirectional, but reverses to the original resistance level when CO was removed from the test chamber. The highest response factor (Delta R/R(0) x 100) and lowest response time (t(50)) obtained are 12 and 169s, respectively. An optimum level of doping (1 mol% of FeTPPCl) was established for the highest sensitivity and the detection level is as low as 100ppm. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: carbon monoxide; Chemical sensor; Fe(III) porphyrin; polypyrrole

Conducting polyaniline-nano-TiO2 composites for smart corrosion resistant coatings - Radhakrishnan, S.; Siju, C. R.; Mahanta, Debajyoti; Patil, Satish; Madras, Giridhar (Electrochimica Acta, 2009)
Coatings prepared from polyaniline-nano-TiO2 particles synthesized by in situ polymerization were found to exhibit excellent corrosion resistance much superior to polyaniline (PANI) in aggressive environments. The corrosion Studies were carried out on steel plates coated with these formulations containing 10 wt% polyaniline prepared with different concentrations of nano-TiO2. The electrochemical impedance spectroscopy was studied at periodic intervals during exposure to hot saline (65 degrees C) conditions for prolonged durations over a period of 90 h. The open circuit potential (OCP) was found to shift with time from -0.38 V SCE to more anodic side (-0.2 V SCE) much above that of bare steel (-0.5 VSCE). The presence of nano-TiO2 was found to be vital in the prevention of corrosion and the shift of OCP to anodic side. From these data, one could envisage more than 100 times improvement in the corrosion resistance especially for polyaniline prepared with 4.18 wt% nano-TiO2. The exceptional improvement of performance of these coatings has been associated with the increase in barrier to diffusion, prevention of charge transport by the nanosize TiO2, redox properties of polyaniline as well as very large surface area available for the liberation of dopant due to nano-size additive. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Anticorrosion; Coating; conducting polymer; Nano-composite; Titanium dioxide